La construcción identitaria de los raperos(as) en los temas de la calle y la protesta. El caso de Morelia, Michoacán (2021)
This article shows the identity construction in the oral discourse of songs created by a representative sector of rappers in Morelia, Michoacán, specifically, based on two themes: the street and the protest. The purpose of this paper is to understand the perception they have of themselves in front of others and in different frames of their pieces. All under the hypothesis that they offer a multidimensional identity in constant change according to their communicative and temporal situation.